PEMBENTUKAN SET JALUR ALIRAN PROGRAM MENGGUNAKAN TEKNIK JUMLAH JALUR MINIMUM DAN TEKNIK JUMLAH PREDIKAT MINIMUM - Rosa de Lima Endang Padmowati (JUTI: Jurnal Ilmiah Teknologi Informasi, 2009)
Structured testing is based on the control flow of programs. The analysis of the control flow of program is conducted on a reduced flowgraph, called a decision-to-decision graph (DDGraph). The relations of dominance and implication between arcs enable to immediate identification of a subset of DDGraph arcs. These arcs are called unconstrained arcs, which have a property that, when the unconstrained arcs are exercised, the traversal of all the other arcs are guaranteed. In order to find a path cover for given program flowgraph, there are two methods: minimum number of paths technique and less pred technique.